Responses to the Practice of Hate Speech at the Pancasila Youth Organization in Sidoarjo - Tis'a Nur Sya’bani; Chusnul Fitriawati; Dewati Yuni Ratnasari; Siti Maizul Habibah (JED (Jurnal Etika Demokrasi), 2021)
The practice of hate speech is not only carried out in the real world but also through the virtual world. The number of suspects in hate speech cases is not foreign to our ears. Based on Police data during 2017, there were 3,325 cases of hate speech crimes. This figure increased 44.99% from the previous year, which amounted to 1,829 cases. Hate speech practices are always motivated by SARA (ethnic, race, religion) issues as Indonesia is a country based on pluralism or upholds diversity. This is to describe the response to the practice of hate speech at the Pancasila Youth Organization on Jl Raya Pahlawan No.82 Jetis, Lemahputro, Sidoarjo. Quantitative research method with data collection techniques through providing questionnaires (questionnaires) and interviews to respondents. The results showed that the response of members of the Pancasila youth organization about the practice of hate speech was quite good. this is also evidenced by the frequency distribution whose value reaches above 75% with the category of quite good in terms of insight into hate speech, and handling hate speech in the community. Praktik ujaran kebencian (hate speech) ini tidak hanya dilakukan  di dunia nyata tetapi juga melaui dunia maya. Banyaknya penetapan tersangka kasus ujaran kebencian (hate speech) tidak asing lagi di telinga kita. Berdasarkan data Polri selama 2017  terdapat 3.325 kasus kejahatan hate speech atau ujaran kebencian. Angka tersebut naik 44,99% dari tahun sebelumnya, yang berjumlah 1.829 kasus Praktik ujaran kebencian (hate speech) selalu di latar belakangi oleh persoalan SARA (suku, ras, agama) sebagaimana indonesia merupakan negara yang berbasis pluralisme atau menjunjung tinggi kebaragaman.Tujuan penelitian ini yaitu untuk menggambarkan tanggapan tentang praktik ujaran kebencian (hatespeech) pada organisasi pemuda pancasila di Jl Raya Pahlawan No.82 Jetis, Lemahputro, Sidoarjo. Metode peneitian kuantitatif dengan keknik pengumpulan data melalui memberikan angket (kuisioner) dan wawancara kepada responden. Hasil penelitian menunjukkan respon anggota organisasi pemuda pancasila tentang praktik ujaran kebencian cukup baik. hal ini juga dibuktikan dengan persebaran frekuensi yang nilainya mencapai diatas 75% dengan kategori  Cukup baik dalam hal wawasan tentang ujaran kebencian, dan penanganan ujaran kebencian di masyarakat.